Capturing innovation in an in-house service deck - Isip, Ronald Fernandez
There is high probability of innovation capture from the service desk as it serves as an interface with the end-users, but finding systematic methods for innovation for technologies supported are seldom available; and just following industry standards (such as with ITIL) may open to the dangers of core rigidity.